Potential application of ivim and dwi imaging in parkinson’s disease - Cruz, Gloria; Nie, Shengdong; Wang, Lijia (Tecnura, 2014)
Parkinson’s disease (PD) is a progressive degenerative neurological condition, which origin remains unclear. We are interested in proposing the study of blood flow in the substantia nigra (SN) in PD patients, based on findings that demonstrated relative hypoactivity in PD patients located to subthalamic nucleus and SN. It is believed that this hipoactivity may suggest changes in the blood flow to the SN, where the particular loss of dopaminergic neurons occurs. The method used is the Incoherent Motion Intravoxel (IVIM) that allows measurement of blood flow to the microvascular level and recently has been producing high resolution quantitative perfusion maps. This paper proposes to measure the perfusion in PD patients and find any correlation with neural activity and water displacements within the tissue. Assuming decreasing the local perfusion suggests the possible impairments that affect the neural activity in PD causing the progressive death of neurons in the SN.